ASSESSMENT OF DRUG COMPLIANCE AMONG HYPERTENSIVE PATIENTS - Akhtar, Yasmin; Afridi, Muhammad Abdur Rahman; Rahman, Zainab; Ali, Zafar (Journal of Postgraduate Medical Institute, 2020)
Objective: To assess the compliance in hypertensive patients to anti-hypertensive medications. Methodology: A descriptive case series study was conducted in the Department of Medicine, Lady Reading Hospital and Khan Memorial Clinic at Abaseen Hospital Dabgari Garden, Peshawar from November 2018 to January 2019.The study included 196 hypertensive patients of both genders above 18 years of age. All hypertensive patients taking antihypertensive medications were included. Demographic and clinical details were recorded regarding duration of hypertension, name, dose and number of drugs being taken and presence of any comorbidity noted. SPSS version 21.0 was utilized for data entry and statistical analysis. Chi-square test at p value â‰¤0.05 at 95% confidence level was considered statistically significant. Results: Among 196 patients, 49 (25%) were male and 147 (75%) were female; with a male to female ratio of 1:3. Age of the patients ranged from 18 to 93 (55.99 ±10.31) years; 120 (61.2%) belonged to 40-60 age group whereas 60 (30.6%) were above 60 years. Overall, 111 (56.6%) patients had poor compliance and 85 (43.4%) had good compliance to medication; 68 (34.7%) were taking beta blockers while 70(35.7%) were on combination of drugs; those on angiotensin II receptor blockers and combinations had better compliance (p=0.001). Conclusion: Majority of the patients in this study were non-compliant to antihypertensive medications. There was no statistical difference between different age groups and gender in relation to compliance. Use of ARBs and drug combinations significantly correlated with good compliance.